2002
DOI: 10.1051/0004-6361:20020662
|View full text |Cite
|
Sign up to set email alerts
|

The WEBT BL Lacertae Campaign 2000

Abstract: Abstract. We present UBVRI light curves of BL Lacertae from May 2000 to January 2001, obtained by 24 telescopes in 11 countries. More than 15 000 observations were performed in that period, which was the extension of the Whole Earth Blazar Telescope (WEBT) campaign originally planned for July-August 2000. The exceptional sampling reached allows one to follow the flux behaviour in fine detail. Two different phases can be distinguished in the light curves: a first, relatively low-brightness phase is followed by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 37 publications
8
131
2
Order By: Relevance
“…Authors also detected hints of bluer-whenbrighter (BWB) trend but any relation between spectral and flux changes were absent. Later, Villata et al (2002Villata et al ( , 2004a confirmed the presence of BWB trend in short isolated outburst but not on long timescales for BL Lacertae, indicating two different components are operating. Heidt & Wagner (1996) found 80% of complete BL Lacerate objects to show IDV confirming it to be their intrinsic nature.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Authors also detected hints of bluer-whenbrighter (BWB) trend but any relation between spectral and flux changes were absent. Later, Villata et al (2002Villata et al ( , 2004a confirmed the presence of BWB trend in short isolated outburst but not on long timescales for BL Lacertae, indicating two different components are operating. Heidt & Wagner (1996) found 80% of complete BL Lacerate objects to show IDV confirming it to be their intrinsic nature.…”
Section: Introductionmentioning
confidence: 86%
“…Collaboration et al 2011). Due to its pronounced variability over entire electromagnetic spectra it has been continuously monitored with Whole Earth Blazar Telescope (WEBT) 1 since 1997 till today; which involves four major WEBT multi-frequency campaigns, two of them were organized in 1999 supplemented with ASCA and Beppo SAX observations (Ravasio et al 2002) (Villata et al 2002;Böttcher et al 2003;Villata et al 2004a,b). Carini et al (1992) studied two optically bright sources, OJ 287 and BL Lacertae using a decade long photometric observations where they found IDV of the order of 0.08 mag/hr in former and 0.01 mag/hr for later.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of BL Lac, these data were complemented by those that were derived from published material from the Whole Earth Blazar Telescope 3 collaboration (WEBT, Villata et al 2002). The collaboration was established in 1997 with the aim of organizing observing campaigns to investigate blazar variability.…”
Section: Light Curvesmentioning
confidence: 99%
“…1 http://www.oato.inaf.it/blazars/webt/ results have been published by Villata et al (2002), Ravasio et al (2002), Böttcher et al (2003), Villata et al (2004b), Villata et al (2004a), Bach et al (2006), Papadakis et al (2007), Villata et al (2009b), Larionov et al (2010).…”
Section: Introductionmentioning
confidence: 99%